The impact of attachment to parents and peers on the psychopathic traits of adolescents: A short longitudinal study - Silva, Diana Ribeiro da (2021)
This work evaluated the cross-sectional and longitudinal (i.e., over four months) impact of attachment to mother, father, and peers on three psychopathic traits (i.e., grandiose-manipulative, callous-unemotional, and impulsive-irresponsible) using a community adolescent sample, and if that impact was differentiated by gender. Though there is evidence for the relevance of attachment on psychopathy, little was derived from adolescent samples or considered diverse attachment figures that play a role in adolescents’ psychosocial development. A sample of 279 adolescents (aged 15 to 21 years; 58.4% female) was asked to self-report on their perceived quality of attachment to parents and peers and on psychopathic traits. Results show evidence for the cross-sectional and longitudinal impact of attachment on psychopathic traits: specifically, attachment to parents is linked with the grandiose-manipulative and impulsive-irresponsible psychopathic traits, whereas attachment to peers relates with the callousunemotional trait. Predictive pathways were overall similar between boys and girls. These results sustain the importance of considering attachment when trying to understand and intervene in antisocial adolescent behavior, namely by adopting a more generalized perspective on who may play a protective role in relation to the development of each psychopathic trait.